Analisis Nilai Waktu Kendaraan Pribadi (Mobil dan Motor) Di Kota Bandar Lampung Dengan Metode Regresi Linear (Studi Kasus : Jalan Kartini) - siburian, Parsaulian; Sulistyorini, Rahayu; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
The value of travel time is the amount of money a person can spend to save a unit of travel time. Loss of travel time is a form of losses in terms of cost and time experienced by road users. This research is conducted at Kartini Street, Bandar Lampung. The purpose of this study is to obtain the value of travel time for car and motorbike users using the linear regression method processed with SPSS. The dependent variable is the cost per length of trip. The independent variables are the lengths, the costs, and the distance of the trip, as well as the socio-economic data of the respondents, namely gender, age, occupation and income. Based on the results of the processing, it is found that the independent variables that have a significant effect on the value of travel time at the research location are age, income, travel time and travel costs. By distributing the mode value of the survey data into the regression equation, the value of travel time on Kartini street for private car drivers is Rp. 25,452.24 / hour and for motorbike riders is Rp. 14,527.26 / hour. Keywords: travel time value, private vehicle, linear regression